IoT System for Detecting Input/Output Patient & Staff via RFID Technology - Chengaou, Sohaib; El Yassini, Khalid; Oufaska, Kenza; Zouadi, Tarik (International Journal of Engineering and Technology, 2018)
The Internet of Things (IoT) is a concept based on several technologies by connecting them to create a network of networks and a system of systems. It is composed of several and different objects such as Smartphone, Smart Watch, Smart refrigerator, Smart tv, etc. And it can guarantee quick access to information, this has had an enormous influence on the pace of contemporary daily life. It is possible to use IoT in critical areas as health for better management of hospital structures or to improve working conditions and staff performance in the hospital domain. This work proposes a solution allowing an improvement in term of management of inputs and outputs of the employees and patients and thus a better management within a hospital.Â Â Â